2015
DOI: 10.2105/ajph.2014.302537
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Texting Bans on Motor Vehicle Crash–Related Hospitalizations

Abstract: We used a panel design and the Nationwide Inpatient Sample from 19 states between 2003 and 2010 to examine the impact of texting bans on crash-related hospitalizations. We conducted conditional negative binomial regressions with state, year, and month fixed effects to examine changes in crash-related hospitalizations in states after the enactment of a texting ban relative to those in states without such bans. Results indicate that texting bans were associated with a 7% reduction in crash-related hospitalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…As for specific age groups, in this analysis driver fatalities were 14% lower for 16–39 year olds, 11% lower for 40–59 year olds, and 8% lower for drivers ≥60 years of age when UHB were effective compared to when they were not. Other studies have similarly reported that UHB were associated with 6–9% lower fatalities amongst 18–54 year old drivers [19], ~8% less for drivers <21 years [18], and 4% less for drivers aged 22–64 years [16]. However, the findings concerning UTB were akin to some studies and dissimilar from others.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…As for specific age groups, in this analysis driver fatalities were 14% lower for 16–39 year olds, 11% lower for 40–59 year olds, and 8% lower for drivers ≥60 years of age when UHB were effective compared to when they were not. Other studies have similarly reported that UHB were associated with 6–9% lower fatalities amongst 18–54 year old drivers [19], ~8% less for drivers <21 years [18], and 4% less for drivers aged 22–64 years [16]. However, the findings concerning UTB were akin to some studies and dissimilar from others.…”
Section: Discussionmentioning
confidence: 81%
“…Two studies concluded that UTB were not associated with significant reductions in total fatal crashes or total fatalities [13, 15]. Another study which investigated the relationship between UTB, total fatalities, and driver fatalities in specific age groups conceded that total fatalities were 5% lower in 15–21 year olds only and driver fatalities were 7% lower only among those ≥65 years when these bans were in effect [16]. However, the findings concerning UHB reveal that their presence were associated with up to 13% lower total fatal crashes, total fatalities, and driver fatalities [13–22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, I account for a host of state- and year-specific policy controls that have been shown to affect motor vehicle fatalities (Dee, Grabowski, & Morrisey, 2005; Ferdinand et al, 2015). In line with previous research, I include beer tax and gasoline prices in 2013 dollars (Cotti and Tefft, 2011; French and Gumus, 2014; Grabowski and Morrisey, 2004; Morrisey and Grabowski, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The authors suggest that the lack of effectiveness of texting bans was due to poor enforcement; drivers refrained from texting immediately after the law's announcement and implementation but returned to texting if they believed the law was not being enforced (Abouk & Adams, 2013). Finally, texting bans were also significantly associated with reductions in hospitalizations among those aged 22 to 64 years and those aged 65 years or older, but did not significantly reduce hospitalizations for adolescents (Ferdinand et al, 2015). While in these analyses it cannot be determined whether the crashes and hospitalizations analyzed were caused by distracted driving or not, these studies suggest that bans with primary enforcement can reduce the burden of injury from cellphone use.…”
Section: Effectiveness Of Current Mitigation Strategiesmentioning
confidence: 99%